New Standards for Providing Meteorlogical and Hydrographic Information Via AIS Application-Specific Messages - Alexander, Lee; Schwehr, Kurt (The International Hydrographic Review, 2010)
AIS Application-specific messages transmitted in binary format will be increasingly used to digitally communicate maritime safety/security information between participating vessels and shore stations. This includes time-sensitive meteorological and hydrographic information that is critical for safe vessel transits and efficient ports/waterways management. IMO recently completed a new Safety-of-Navigation Circular (SN/Circ.) that includes a number of meteorologi-cal and hydrographic message applications and data parameters. In conjunction with the development of a new SN/Circ., IMO will establish an International Application (IA) Register for AIS Application-Specific Messages. IALA plans to establish a similar register for regional appli-cations. While there are no specific standards for the presentation/display of AIS application-specific messages on shipborne or shore-based systems, IMO issued guidance that includes specific mention of conforming to the e-Navigation concept of operation. For both IHO S-57 and S-100-related data dealing with dynamic met/hydro information, it is recommended that IHO uses the same data content fields and parameters that are defined in the new IMO SN/Circ. on AIS Application-specific Messages.